(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the outcomes of laparoscopic seminal vesicle cyst excision in patients presenting with hematospermia and to review the literature on the rare Zinner syndrome. Subjects and methods: A retrospective cross-sectional descriptive study was conducted on two male patients with hemorrhagic seminal vesicle cysts who underwent laparoscopic surgery at 108 Military Central Hospital and Viet Duc University Hospital. Clinical characteristics, imaging findings, operative details, perioperative outcomes, and postoperative follow-up data were analyzed. Results: Patient 1 was a 16-year-old male diagnosed with a left seminal vesicle cyst measuring 60 × 40 mm associated with left renal agenesis and a solitary right kidney. Laparoscopic excision was performed using four trocars (three 10-mm and one 5-mm trocars). Operative time was 90 minutes with blood loss less than 50 ml. No intraoperative complications occurred. The patient was discharged after 5 days. Histopathology revealed a seminal vesicle cyst with chronic fibrotic stromal inflammation. Patient 2 was a 24-year-old male diagnosed with a right seminal vesicle cyst measuring 70 × 35 mm associated with right renal agenesis and a solitary left kidney. Surgery was completed laparoscopically using four trocars (two 10-mm and two 5-mm trocars). Operative time was 95 minutes with negligible blood loss. No intraoperative complications were observed. Length of hospital stay was 5 days. Histopathological examination demonstrated a benign seminal vesicle cyst with fibrotic connective tissue. At 6-month follow-up, hematospermia resolved completely in both patients; however, semen analysis showed decreased sperm quantity and quality. Conclusion: Seminal vesicle cysts are rare lesions commonly associated with Zinner syndrome. Cysts larger than 5 cm are more likely to cause clinical symptoms. Laparoscopic excision is a safe and effective minimally invasive treatment for symptomatic seminal vesicle cysts. Zinner syndrome may adversely affect male fertility despite successful surgical management.